Effective development of the modern economy: problems and prospects - Baranova N. A., Kruglov V. N., Kulakova S. V., Kul'chikova Z. T., Lebedev V. E., Lilimberg S. I., Panina G. V., Vinogradova N. P., Lilimberg S. I., Selezniova T. O., Maer O. I., Malanina A. A., Mfliarenko O. I., Baikova E. I., Minakov A. V., Agapova T. N., Minitaeva A. M., Mishulina O. V., Gorelova N. S., Odinokova T. D., Sokheilinia K., Shpak A. S., Shcherbakova N. S., Tuzandekhdzhani M. (Effective development of the modern economy: problems and prospects, 2025)
in the context of growing cultural diversity, conflict management in multinational organizations is becoming one of the key tasks of HR management. The authors conducted a systematic analysis of theoretical approaches to conflict management, reviewed modern conflict management strategies and identified the specifics of their application in the Russian context. The research is based on the method of systematic literature review and comparative analysis. Special attention is paid to the role of HR managers in conflict prevention and resolution, as well as practical recommendations for creating an effective corporate culture in the context of intercultural interaction. The conclusions made by the authors can be useful for heads of organizations, HR specialists and researchers dealing with personnel management issues in multinational teams.
Keywords: коммуникация; доверие; communication; управление конфликтами; mediation; trust; conflict management; кросс-культурный менеджмент; посредничество; переговоры; профилактика конфликтов; методы разрешения конфликтов; конфликтология; многонациональные организации; межкультурные конфликты; стратегии сотрудничества; multinational organizations; intercultural conflicts; conflictology; conflict resolution methods; negotiation; cross-cultural management; collaboration strategies; conflict preventio